The Effect of Ergonomic Principles Education on Musculoskeletal Disorders among Computer Users - Tahereh Yektaei; Farhad Tabatabaei-Ghomsheh; Leila Piri (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The aim of this study was to evaluate the education ergonomic principles on musculoskeletal disorders among computer users at Rasht welfare organization in 2011. Materials & Methods: This semi-experimental study, 283 female computer users whom had musculoskeletal disorders randomly assigned into two groups. The case group were educated practically and theoretically about ergonomic issues for three months and ergonomic interventions were carried out for this group. Body map questionnaire was used for estimation of musculoskeletal disorders level and statistical analysis was performed using kolmogorov-smirnov and covariate test. Results: The results of the present study showed that the highest prevalence rate of musculoskeletal disorders were reported in right knee (27.91%), neck region (27.20%) , lumbar and right shoulder (24.14%), left knee (25.79%), back (23.67%). The results of this research showed that there was homogeneity of variance and the meaning of the F covariance at the level of P&le0.05 revealed that the education of ergonomic principles leads to a reduction of Musculoskeletal Disorders among computer users. Conclusion: Education of ergonomic principles for the computer users and ergonomic interventions like correction of postures, reducing of work duration , armrest, foot rest, and cushion strengthening exercise and regulating of work station application have a significant effect on the decreasing musculoskeletal disorders prevalence among computer users.